A new species of Sericothripinae from China (Thysanoptera: Thripidae), with two new synonyms and one new record - Mirab-Balou, Majid; Hu, Qing-Ling; Feng, Ji-Nian; Chen, Xue-Xin (Zootaxa, 2011)
One new species of subfamily Sericothripinae (Thysanoptera: Thripidae) is described and illustrated: Hydatothrips longjingensis sp. n., and H. abdominalis (Kurosawa) is newly recorded from China. The following taxonomic changes are established: Sericothrips houji (Chou & Feng) comb. n. (from Hydatothrips).